2014
DOI: 10.1007/s00586-014-3697-9
|View full text |Cite
|
Sign up to set email alerts
|

Same-species phenotypic comparison of notochordal and mature nucleus pulposus cells

Abstract: NC and MNP cells can be isolated from the same bovine disc and maintain their distinct phenotypes in 3D culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…T is an embryonic transcription factor required for mesoderm formation and differentiation and notochord‐development . This protein has often been used as a marker of a notochordal phenotype . In our study, T was found to be expressed by all notochordal cells at all stages analyzed, which suggests that this transcription factor has a role in human notochordal cell development.…”
Section: Discussionsupporting
confidence: 61%
“…T is an embryonic transcription factor required for mesoderm formation and differentiation and notochord‐development . This protein has often been used as a marker of a notochordal phenotype . In our study, T was found to be expressed by all notochordal cells at all stages analyzed, which suggests that this transcription factor has a role in human notochordal cell development.…”
Section: Discussionsupporting
confidence: 61%
“…Due to the broad donor age range used in this study (1-8.5 years old), NP tissue may contain varying amounts of notochordal cells (NC). It has been suggested that up to 10% of bovine NP cells per tail IVD are NC, based on size exclusion and/or Keratin 8 expression [17,24]. The latter study used 18-24 month old bovine donors, while the former study did not report donor age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, model organisms, such as the cow, are used for in vitro cellular and ex vivo biomechanical studies of the IVD [14,15]. The bovine tail IVD represents a good model for the non-degenerate human IVD: the bovine NP retains few notochordal cells and whole transcriptome analyses identified similar phenotypic marker genes as in humans [6,16,17]. This study aimed to establish whether IVD phenotypic marker genes, which we previously used to distinguish non-degenerate human NP from AF cells, can be used to describe the cell phenotype in the outer AF, inner AF and NP in situ in the bovine tail IVD and this was compared to passage 0 monolayer cells.…”
Section: Introductionmentioning
confidence: 99%
“…NC-conditioned medium (NCCM, containing factors secreted by NCs) and NC:CLC co-culture stimulate in vitro differentiation of MSCs into a NP-like phenotype Korecki et al, 2010;Purmessur et al, 2011), protect the NP from apoptosis (Erwin et al, 2011;Mehrkens et al, 2013), and/or increase CLC proliferation and GAG production (Abbott et al, 2012;Aguiar et al, 1999;Gantenbein et al, 2014;Potier et al, 2014). In addition, NCs significantly stimulate CLC activity and GAG production (Gantenbein-Ritter et al, 2012) and produce more GAGs than CLCs (Saggese et al, 2014). NCs have also been described to exert potential symptom modifying actions, e.g.…”
Section: Ncs Of Different Species Regenerate Human Clcsmentioning
confidence: 99%